The Effect of Work Discipline and Competence on Job Satisfaction And its impact on the performance of employees of the Class I Palembang Radio Frequency SpectrumMonitor Center - Marulam Damanik; Djatmiko Noviantoro; Sari Sakarina (CV Putra Publisher, 2025)
This study basically aims to determine the effect of work discipline and competence on job satisfaction and its impact on the performance of employees of the Class I Palembang Radio Frequency Spectrum Monitor Center. In writing this thesis, the author uses primary data collection techniques, which are obtained by distributing questionnaires. this research uses path analysis and uses the Smart PLS 3.0 statistical application. with a sample of 35 respondents. The results showed that there was an effect of work discipline and competence on job satisfaction and its impact on employee performance at the Palembang Class I Radio Frequency Spectrum Monitor Center, with the equation Y = 0.666X1 + 0.605X2 + ɛ1, and the equation Z = 0.356X1 + 0.409X2 + 0.321Y + ɛ2, there is an effect of work discipline on employee job satisfaction at the Palembang Class I Radio Frequency Spectrum Monitor Center. This is indicated from the Original Sample value of 0.666 with a T-Statistic value of 4.466> 1.96, the P-Value is 0.000 < 0.05, there is an effect of competence on employee job satisfaction at the Palembang Class I Radio Frequency Spectrum Monitor Center, indicated from the Original Sample value of 0.605 with a T-Statistic value of 3.543> 1.96, the P-Value is 0.000 < 0.05, there is an effect of work discipline on employee performance at the Palembang Class I Radio Frequency Spectrum Monitor Center, indicated from the Original Sample value of 0.356, 356 with a T-Statistic value of 2.547> 1.96, the P-Value is 0.011 < 0.05, there is an effect of competence on the performance of employees of the Palembang Class I Radio Frequency Spectrum Monitor Center, indicated by the Original Sample value of 0.409 with a T-Statistic value of 2.793> 1.96, The P-Value is 0.005 < 0.05, there is an effect of job satisfaction on the performance of employees of the Radio Frequency Spectrum Monitor Class I Palembang, indicated by the Original Sample value of 0.321 with a T-Statistic value of 1.981 > 1.96, the P-Value is 0.045 < 0.05.